Effect of processed bambara groundnuts and benne seeds on growth and organ morphology of broiler (Bangladesh Journal of Animal Science, 2015)
An experiment was conducted to determine the effects of replacing full fat soybean meal with aqueousheated, dryheated and dehulled Bambara groundnuts (Vigna subterranea (L.) Verdc.) and benne seeds (Sesamum indicum) on performance characteristics and organ morphology of broiler chickens over a period of eight weeks. Anti-nutritional factors in the raw and processed plant seeds were determined. Higher amounts of haemagglutinin (HG) and trypsin inhibitor (TI) were found in the raw Bambara groundnuts, and tannin, phytate and oxalate in raw benne seeds  respectively. Both HG and TI were completely destroyed in aqueous-heated Bambara groundnuts while the dry heated Bambara groundnuts contained residual amounts of the anti-nutrients. Higher amounts of the tannin, oxalate and phytate were removed in the dehulled benne seeds. Feed intake was statistically not significant in different treatment groups. Weight gain and feed conversion efficiency were more significantly (p